Shore-based Counts of Bowhead Whales along the Chukotka Peninsula in May and June 1999-2001 - Melnikov, V.V.; Litovka, D.I.; Zagrebin, L.A.; Zelensky, G.M.; Ainana, L.I. (ARCTIC, 2004)
This study presents the results of shore-based counts of bowhead whales (Balaena mysticetus) along the Chukotka Peninsula in 1999, 2000, and 2001. These counts confirmed that at least a small proportion of the Bering-Chukchi-Beaufort Seas stock migrates along the western Bering Strait in late spring. The results of the counts in the Bering Strait were somewhat consistent between years. Taking into account that the whales passed by rapidly at great distances, we believe the number of whales seen during these counts is an underestimate of the actual number of whales migrating through the area. Our results indicate that the beginning of the spring migration of bowhead whales out of the Gulf of Anadyr varies by up to 30 days between cold and mild years, but in both cases, the area migration continues at least until 20 June. During the spring migration in the western Bering Strait, at the exit from the Gulf of Anadyr, whales moved over a broad front from near shore out to sea. When the directed migration began in May, the whales were not (or were seldom) observed to rest, feed, or engage in social behavior. Instead, we saw whales traversing long distances under water, swimming at speeds considerably faster than those of bowhead whales noted previously at Point Barrow. Cette étude présente les résultats de dénombrements côtiers de baleines boréales (Balaena mysticetus) effectués le long de la presqu'île des Tchouktches en 1999, 2000 et 2001. Ces comptages ont confirmé qu'au moins une petite proportion du stock de la mer de Béring, de la mer des Tchouktches et de la mer de Beaufort migre à la fin du printemps le long du détroit de Béring occidental. Les résultats des dénombrements dans le détroit de Béring étaient relativement uniformes d'une année à l'autre. Si l'on tient compte du fait que les baleines passaient rapidement, et ce, à une grande distance, on pense que le nombre des baleines aperçues durant ces comptages représente une sous-estimation du nombre réel de ces cétacés qui traversent la région durant leur ...